Factors underlying students' decisions to use mobile devices in clinical settings. (30th August 2017) - Harrison, Amanda; Phelps, Megan; Nerminathan, Arany; Alexander, Shirley; Scott, Karen M.
Abstract: University policies prohibiting use of mobile devices by medical students during clinical placements are contradicted by regular use by physicians. Consequently, many students use their mobile devices, which can be beneficial for learning but may put patient privacy at risk. This study explores the reasons underlying students' decisions about using mobile devices in clinical settings. We used a mixed‐methods sequential explanatory design involving a questionnaire and focus groups. Qualitative data from the questionnaire and focus groups was analysed through thematic analysis. We found students were aware of the risks mobile devices posed to professionalism and medical practice. Despite prohibitions, many made individual decisions to use mobile devices because the benefits outweighed the risks. These students were influenced by an organised, strategic approach to learning and a motivation to comply with the beliefs and behaviours of their medical teams and conform to physicians' directives in order to participate in their community of practice. Many students appear to be transferring everyday use of mobile devices to clinical settings. There is a need to understand and promote aspects of learning that are enhanced by mobile devices in clinical settings, while articulating clear guidelines and boundaries compatible with the professional behaviour expected of students.